2021
DOI: 10.46222/ajhtl.19770720-101
|View full text |Cite
|
Sign up to set email alerts
|

Research Trends and Perspectives on Domestic Tourism in Kenya: A Review

Abstract: The quantity and quality of research output available on the subject of domestic tourism in Kenya is yet to be sufficiently documented. This review evaluates trends in the studies carried out on this subject and establishes perspectives revealed in these studies' findings. Methodologically, this is a conceptual review of integrative nature in which the reviewer summarized the findings of other studies conducted on domestic tourism in different parts of Kenya. Both published and unpublished works addressing dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Before Covid-19 WTTC (2018) reported that this form of tourism was a significant source of tourism earnings in China, Brazil, India, Argentina and Germany, as well as Japan, Mexico, the UK and the US. Despite being a notable destination in Africa, Kenya in the past appeared to over-rely on international tourism (Manono & Rotich, 2013;MToW, 2018;Osiako & Szente, 2021). The tourism sector is a major economic contributor to the country's Gross Domestic Product (GDP) at 10.4% and directly employs 990,000 jobs (TRI, 2021).…”
Section: Basic Indicators Of Domestic Tourism In Kenyamentioning
confidence: 99%
See 1 more Smart Citation
“…Before Covid-19 WTTC (2018) reported that this form of tourism was a significant source of tourism earnings in China, Brazil, India, Argentina and Germany, as well as Japan, Mexico, the UK and the US. Despite being a notable destination in Africa, Kenya in the past appeared to over-rely on international tourism (Manono & Rotich, 2013;MToW, 2018;Osiako & Szente, 2021). The tourism sector is a major economic contributor to the country's Gross Domestic Product (GDP) at 10.4% and directly employs 990,000 jobs (TRI, 2021).…”
Section: Basic Indicators Of Domestic Tourism In Kenyamentioning
confidence: 99%
“…This has both been caused by and resulted from accelerated local leisure-related activities, especially in and adjacent to major urban centers such as Nairobi, Nakuru, Mombasa, Kisumu and Eldoret. Earlier studies carried out on domestic tourism in Kenya have exhibited a paucity of comprehensiveness in scope and content, leaving many aspects of domestic tourism in need of research attention (Osiako & Szente, 2021).…”
Section: Basic Indicators Of Domestic Tourism In Kenyamentioning
confidence: 99%
“…Furthermore, domestic tourism plays an important role in a country's economic development because it supports formal, small-scale enterprises and informal sectors (Rwigema, 2024). It tends to lead to an increase in employment, improve the host community's standard of living, and develop attractions (Murima and Shereni, 2023). However, in some cases, domestic tourism has been neglected both as an area of development and as a subject of research (Rwigema, 2024), particularly in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Africa as a continent is yet to exploit her tourism potential fully, despite her tourism industry playing a key role in the global economy (KIPPRA, 2017). Among the Africa countries striving to improve both domestic and international tourism is Kenya (Manono and Rotich, 2013;Ministry of Tourism and Wildlife, 2018), doing this in an effort to dispel the common notion that the country heavily recognizes foreign tourism at the expense of domestic tourism (Osiako and Szente, 2021). The domestic tourism council of Kenya (DTCK) was created in 1984 with the mandate of promoting tourism to a higher notch (Gachenge, 2007).…”
Section: Introductionmentioning
confidence: 99%